How offshoring can affect the industries' skill composition - Daniel Horgos; Lucia Tajoli (Economies, 2015)
While most of the offshoring literature focuses on the effects on relative wages, other implications do not receive the necessary attention. This paper investigates the effects on the industries' skill ratio. It summarizes the empirical literature, discusses theoretical findings, and provides empirical evidence for Germany. As results show, effects are mainly driven by the industry where offshoring takes place. If offshoring takes place in high-skill intensive industries, the high-skill labor ratio increases (vice versa if offshoring takes place in low-skill intensive industries). Results are in line with other empirical findings, however, they seem to contradict theoretical causalities. Thus, we additionally discuss possible explanations.
Keywords: F16; J21; 330; offshoring; labor market implications; skill ratio; skill composition